2008
DOI: 10.1101/gr.087775.108
|View full text |Cite
|
Sign up to set email alerts
|

MEN ε/β nuclear-retained non-coding RNAs are up-regulated upon muscle differentiation and are essential components of paraspeckles

Abstract: Studies of the transcriptional output of the human and mouse genomes have revealed that there are many more transcripts produced than can be accounted for by predicted protein-coding genes. Using a custom microarray, we have identified 184 non-coding RNAs that exhibit more than twofold up-or down-regulation upon differentiation of C2C12 myoblasts into myotubes. Here, we focus on the Men e/b locus, which is up-regulated 3.3-fold during differentiation. Two non-coding RNA isoforms are produced from a single RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
666
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 600 publications
(693 citation statements)
references
References 50 publications
23
666
1
3
Order By: Relevance
“…There may be classes of lincRNAs that function in entirely different ways. For example, the lincRNAs NEAT1 and NEAT2 have been recently shown to be important in the formation of paraspeckles (25), and the lincRNA NRON has a role in repressing nuclear import (26). It is possible that additional lincRNAs have roles in these and numerous other cellular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There may be classes of lincRNAs that function in entirely different ways. For example, the lincRNAs NEAT1 and NEAT2 have been recently shown to be important in the formation of paraspeckles (25), and the lincRNA NRON has a role in repressing nuclear import (26). It is possible that additional lincRNAs have roles in these and numerous other cellular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no floating cells (dead cells) were seen by depletion of NR_015389, AK091718, and AK055657 under microscopic observation (data not shown), suggesting that these SLiTs are modifying factors but are not essential for cell proliferation. Biochemical fractionation indicated that NR_015389, AK091718, AK055657, AK123363, and NR_033895 were predominantly enriched in the heavy fractions of the sucrose density-gradient analysis, along with nuclear lncRNAs, such as NEAT1 (Clemson et al 2009;Sasaki et al 2009;Sunwoo et al 2009) and MALAT1, which are components of nuclear bodies ( Fig. 5B; Supplemental Fig.…”
Section: Bric-seq Reveals Hundreds Of Slits In Mammalsmentioning
confidence: 99%
“…A similar mechanism has been reported for two tRNA-like molecules generated from the mammalian lncRNAs MALAT1 and Menβ . In both cases, RNase P recognizes the tRNA-like structure in a nascent RNAPII transcript and cleaves it to simultaneously generate the 3′-end of the mature nuclear-retained lncRNA and the 5′-end of the tRNA-like small RNA [31, 32]. Recently, 132 genomic loci resembling the MALAT1 3′-end processing module have been identified among several vertebrate genomes [33].…”
Section: Discussionmentioning
confidence: 99%